Propuesta de Sitio Web Accesible para Personas con Discapacidad Visual - Ortega, Maricela Pinargote; Felipe, Marely del Rosario Cruz; Ureta, Gabriel Demera (KnE Engineering, 2018)
The Technical University of Manabí (UTM) (Ecuador) provides support to people with priority attention, currently has registered: 36 students, 3 teachers and 8 employees with visual impairment. The present work proposes to transform the website of the Unit for Inclusion, Social Equity and Gender (UIESG) into accessible based on accessibility standards; where the community in general and university with visual impairment enjoy in equal conditions different alternatives: configure the screen with increasing or decreasing the size of the text, activate voice, use screen reader programs that read the alternative text of the images And correctly describe the content, and change the background color in contrast to the text; contributing to the inclusive progress of this university. Keywords: Ecuador, university, visual impairment, website, accessibility.